Ultrathin film coating of hydroxyapatite (HA) on a magnesium–calcium alloy using RF magnetron sputtering for bioimplant applications; Materials Letters; Vol. 152 - Surmeneva M. A. Maria Alexandrovna; Mukhametkaliev T. M. Timur Mukhamedrashidovich; Khakbaz Hadis; Surmenev R. A. Roman Anatolievich; Kannan M. B. M. Bobby (2015, 2015)
Title screen